Outcomes of endosutured aneurysm repair with the Heli-FX EndoAnchor implants. (October 2020) - Karaolanis, Georgios; Antonopoulos, Constantine N; Koutsias, Stylianos; Antoniou, George A; Beropoulis, Efthymios; Torsello, Giovanni; Taneva, Gergana T; Donas, Konstantinos P
Objective: Endovascular aneurysm repair has gained field over open surgery for the treatment of abdominal aortic aneurysm. However, type Ia endoleak represents a common complication especially in hostile neck anatomy that is recently faced using endoanchors. We conducted a systematic review and meta-analysis to collect and analyse all the available comparative evidence on the outcomes of the endosuture aneurysm repair in patients with or without hostile neck in standard endovascular aneurysm repair. Methods: The current meta-analysis was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. All the prospective and retrospective studies reporting primary use of the Heli-FX EndoAnchor implants were considered eligible for inclusion in this study. The main study outcomes (technical success of endoanchor implantation, incidence of type Ia endoleak, aortic stent graft migration and the percentage of patients who presented regression or expansion of aneurysm sac throughout the follow-up) were subsequently expressed as proportions and 95% confidence intervals. Results: Eight studies with a total of 968 patients were included in a pooled analysis. The technical success of the primary endoanchor fixation was 97.12% (95%CI: 92.98–99.67). During a mean six months follow-up period, a pooled rate of 6.23% (95%CI: 0.83–15.25) of the patients developed a persistent type Ia endoleak despite the primary implantation. Migration of the main graft was reported in five studies, in which a 0.26% (95%CI = 0.00–1.54) of the patients required an additional proximal aortic cuff. Regression of the aneurysm sac was observed at 68.82% (95%CI: 51.02–84.21). An expansion of the aneurysm sac was found in 1.93% (95%CI: 0.91–3.24) of the participants. The overall survival rate was 93.43% (95%CI: 89.97–96.29) at a mean six months follow-up period. Conclusions: Endosuture aneurysm repair with the Heli-FX EndoAnchor implants seems to be technically feasible and safe either for prevention or for repair of intraoperative type Ia endoleak. Despite the primary implants of endoanchors, few cases of persistent type Ia endoleak and migration are still conspicuous. Long-term follow up is needed to determinate the role of this therapeutic option in the treatment of aortic aneurysms.